A SWOT Analysis of Remote Working Based on Review of Literature - P.D. Karunarathne (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The extant literature on ‘remote working’ have mostly focused on its advantages, disadvantages and consequences from the employer, employee & social perspectives as separate parameters with little research exploring the context of remote working from an overall strategic management perspective. The fear and threat evolved from the COVID -19 pandemic have urged tens of millions of global workforce to work from home which was a way of working that had struggled to gain traction before the pandemic. In this ‘new normal’ there is a significant tendency for the remote working to continue in the long run which requires organizations to strategically plan and implement the remote working culture. In consistent with the strategic planning, this review paper explores the existing literature and aims to identify a SWOT Analysis of remote working that would be useful for the current ‘new normal’ context. The thematic analysis approach has taken and through that, four themes have identified and defined from the literature review towards achieving objective of the paper. Literature from the conceptual & empirical studies conducted over the past two decades on remote working have been considered for the review.